Effects of work environment on transfer of training: empirical evidence from Master of Business Administration programs in Vietnam. (6th December 2012) - Pham, Nga T. P.; Segers, Mien S. R.; Gijselaers, Wim H.
<x xml:space="preserve">Abstract</x> Practical application of newly gained knowledge and skills, also referred to as transfer of training, is an issue of great concern in training issues generally and in Master of Business Administration (MBA) programs particularly. This empirical study examined the influence of the trainees' work environment on their transfer of training, taking into account the role of trainees' transfer strategies. The study was conducted on 167 trainees from eight MBA programs in Vietnam in 2007–2008. Path analysis and structural equation modeling were applied to examine the effects of potential factors on transfer of training. The results showed that work environment factors such as supervisory support, job autonomy and preferred support (support as needed by the trainee) were significantly associated with the training transfer. Additionally, trainee's use of transfer strategies mediated the work environment and training transfer relationship.